An experimental investigation of the solubility and speciation of scandium in fluoride-bearing aqueous liquids at temperatures up to 250 °C. (1st August 2022) - Wang, Jiaxin; Williams-Jones, A.E.; Timofeev, A.; Liu, Jiajun; Yuan, Shunda
Abstract: The solubility of ScF3 (solid) and the speciation of scandium in fluoride-bearing aqueous solutions with HF concentrations from 0.53 mmol/kg to 645.12 mmol/kg were investigated at temperatures from 100 to 250 °C and vapor-saturated water pressure. The results of the experiments show that ScF2 + and ScF3 o are the dominant species in fluoride-bearing solutions at the conditions investigated. The logarithms of the formation constants (log β) for these species have been determined for 100, 150, 200, and 250 °C and show that scandium fluoride complexes are more stable than scandium hydroxide complexes and Sc 3+ at these temperatures in acidic aqueous fluids. Whether this is also the case for near-neutral and alkaline conditions remains to be investigated. Modeling of the transport and deposition of scandium using our experimental data provide evidence that fluoride-bearing aqueous fluids can dissolve up to 2.9 ppm scandium at 250 °C, 500 bar, and a pH of 3, which is more than sufficient to form a hydrothermal ore deposit, given that concentrations of several hundred ppm in a deposit are considered economic. This study reports the essential thermodynamic data needed to understand the factors that control the mobilization of scandium in fluoride-bearing hydrothermal systems and determine whether scandium can be concentrated to exploitable levels.